2009
DOI: 10.1007/s10751-009-9928-5
|View full text |Cite
|
Sign up to set email alerts
|

Ion bombardment of Fe-based amorphous metallic alloys

Abstract: Fe 74 Cu 1 Nb 3 Si 16 B 6 amorphous metallic alloy is investigated after ion irradiation by 110 keV N + and 593 MeV Au ions. The depth-profiles of the radiation damage were calculated by the SRIM2008 code. Applicability of transmission and conversion electron Mössbauer effect measurements to distinguish between the bulk and surface radiation damage is demonstrated by using different irradiation conditions. The investigated alloy is characterized by ferromagnetic interactions. The implantation does not depict a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…TMS of the samples irradiated with 593 MeV Au ions exhibited changes in orientation of the net magnetic moment at 1 × 10 12 ions/cm 2 [5], which is a fluence causing the radiation damage due to nuclear stopping of less than 0.01 dpa (Fig. 1).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…TMS of the samples irradiated with 593 MeV Au ions exhibited changes in orientation of the net magnetic moment at 1 × 10 12 ions/cm 2 [5], which is a fluence causing the radiation damage due to nuclear stopping of less than 0.01 dpa (Fig. 1).…”
Section: Resultsmentioning
confidence: 98%
“…Samples of Finemet irradiated by 110 keV N ions showed changes in spectral parameters, especially in isomer shift, at 2 × 10 16 ions/cm 2 [5]. This is the fluence that causes radiation damage of dpa > 10 due to elastic nuclear stopping.…”
Section: Resultsmentioning
confidence: 99%
“…The study is a part of a complex long-term research programme devoted to studying the influence of radiation on magnetic metallic alloys. In addition to heavy ions, this programme includes also neutrons (6) and light ions (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…However, results obtained during the last two decades pointed out that irradiation did induce modifications of MGs properties. In particular, it has been observed that the specimen geometry [5,6], thermal stability and crystallization process [7], magnetic anisotropy [8], shape of hysteresis loops [9], magnetic susceptibility [10,11] and mechanical characteristics such as strength [12] of MGs can be affected by ion irradiation. Such changes might lead to a malfunction of devices that use MGs if operated, for example, in a new generation of high-power, heavy-ion accelerators.…”
Section: Introductionmentioning
confidence: 99%